2021
DOI: 10.1002/ncp.10733
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐week peptide‐based formula therapy may be effective in inducing remission of active Crohn disease among women who are pregnant or preparing for pregnancy

Abstract: Background: Conventional treatment for Crohn disease (CD) in pregnancy includes mesalamine, thiopurine, and anti-tumor necrosis factor (TNF)-α agents. However, women may abstain because of complications, nonresponse, or potential adverse outcomes. Peptide-based formula therapy, through oral or nasogastric feeding without other food intake, is an effective and safe therapy for active CD. Herein, We confirmed the effectiveness and safety of peptide-based formula therapy for active CD in pregnant women or those p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Hence, this provides the rationale for a safe and effective alternative to conventional therapeutic strategies to induce clinical remission during pregnancy. 59 A recent retrospective analysis, conducted in 31 adults, described a significant improvement of clinical symptoms and biochemical parameters after a median duration of 4 weeks of EEN in adult patients with complicated CD. 60 It is noteworthy that among different phenotypes of CD, more than 80% patients had either stricturing or fistulizing disease.…”
Section: Exclusive Enteral Nutrition In Adult Crohn’s Disease Patientsmentioning
confidence: 99%
“…Hence, this provides the rationale for a safe and effective alternative to conventional therapeutic strategies to induce clinical remission during pregnancy. 59 A recent retrospective analysis, conducted in 31 adults, described a significant improvement of clinical symptoms and biochemical parameters after a median duration of 4 weeks of EEN in adult patients with complicated CD. 60 It is noteworthy that among different phenotypes of CD, more than 80% patients had either stricturing or fistulizing disease.…”
Section: Exclusive Enteral Nutrition In Adult Crohn’s Disease Patientsmentioning
confidence: 99%
“…A meta-analysis including five randomized clinical trials that compared the effect of EEN with corticosteroids suggested that EEN was as efficacious as corticosteroids ( 8 ). Studies performed at our center have demonstrated that EEN is equally effective as steroids and biologics for inducing early clinical remission in adult patients with CD, particularly in complicated cases, such as those with intestinal fistulas, abdominal abscesses, inflammatory intestinal strictures, or treatment resistance ( 9 , 10 ). Specifically, EEN promotes mucosal healing (MH) and fistula closure and reduces abdominal abscess size.…”
Section: Introductionmentioning
confidence: 99%